Urbanizations and public spaces in Lima: San Isidro, Chorrillos and Miramar. 1919-1930 - Quispe, Fredy (2021)
The city of Lima had an accelerated urban development during the Oncenio of Leguía (1919- 1930). The urban area doubled and the triangle formed between Lima, Callao and Chorrillos began to be occupied. Leguía, Costanera and El Progreso avenues consolidated urban development and more than thirty urbanizations were projected. San Isidro, Chorrillos and Miramar were built in this period and were oriented to different socioeconomic levels. The San Isidro urbanization is located around the Olivar forest, the Chorrillos urbanization has as a reference the solar hill and the Miramar urbanization faces the ocean South Pacific. The urbanizations developed during this period did not project new areas for public spaces or green areas, and may partly explain the current absence of squares, parks, recreation areas and spaces for citizen affirmation that the capital suffers from.